THE EFFECTIVENESS OF USING PICTURE - GUESSING GAME IN WRITING SKILLS - Muttoharoh, Siti; Agustina, Ria Kamilah (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
Most of students feel bored in learning to write, one of the reasons is because the teaching and learning process still uses the teacher centered method. Thus, with the decline in learning achievement in writing, it seems that writing is difficult and boring. Therefore, the researcher used the picture guessing game media as a solution to the problem. The puposes in this study are to know the students’ before and after being taught using picture guessing game and to know the significant effect of using picture guessing games on students' writing skills at class 7D MTs Salafiyah Syafiiyah. The findings in this study are The student's score before being taught picture guessing game is still low and is included in the Enough score qualification. Then, the posttest scores of students after being taught the picture guessing game got an increase and were included in the qualification of good scores. The data shows that sig. (2-tailed) was 0.000. It was lower than 0.05. The results of these calculations mean that there is a significant effective of students' writing skills using the picture- guessing game. Thus, it can be concluded that the picture-guessing game is effective in teaching students' writing skills. So, it is strongly recommended for the teacher to use this media in writing class.